Examining access to sexual and reproductive health services and information for young women with disabilities in Senegal: a qualitative study - Olivia Soule; Diatou Sonko (Sexual and Reproductive Health Matters, 2022)
This qualitative research aimed to examine Senegalese disabled women’s access to sexual and reproductive health (SRH) services and information. Poor access to SRH services and information can lead to a range of negative consequences, including poor sexual, reproductive, and maternal health outcomes; rights violations; and impacts on mental health and livelihoods. Disabled women, who are marginalised and stigmatised both by their gender and their disability, may face significant barriers in access, but a full understanding of this access is lacking due to a dearth of research on this population. We used a snowball sampling method to identify 31 women with physical motor disabilities in the Dakar region, and we interviewed them from October to December 2019 using a semi-structured questionnaire. We analysed interviews using thematic analysis, which we complemented with frequency calculations and graphs where appropriate. Respondents reported having difficulties accessing SRH services and information because of structural inaccessibility within health care establishments, financial limitations, inaccessible transportation and far-away health establishments, long wait times in health care establishments, and prejudices and discrimination from health providers. Women had low knowledge of STIs, but were generally well-informed on different types of contraception, felt that accessing SRH information is easier than accessing services, and wished to see improvements in the Senegalese health care system specifically geared towards people with disabilities. Evidence from this research can inform policy and programmatic efforts to improve disabled women’s access to SRH services and information.